Perbuatan Melawan Hukum oleh Notaris dalam Melakukan Legalisasi Surat Hibah yang Dibuat dalam Keadaan Terpaksa: Studi Putusan Pengadilan Negeri Kisaran Nomor 51/Pdt.G/2023/PN.Kis jo. Putusan Pengadilan Tinggi Medan Nomor 157/Pdt/2024/PT.Mdn - Nicholas Teo Pan; hasim purba; Mahmud Mulyadi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The validity of a deed of gift legalized by a Notary under coercion must be examined based on Article 1320 of the Indonesian Civil Code, particularly regarding the requirement of free consent. A study of the Decision of the Medan High Court Number 157/Pdt/2024/PT.Mdn in conjunction with the Decision of the Kisaran District Court Number 51/Pdt.G/2023/PN.Kis shows that legalization only guarantees formal aspects and does not eliminate defects of consent. A Notary may be qualified as committing a tort if they neglect their duties in accordance with the Law on Notary Position. The judges’ legal considerations are deemed appropriate as they are based on evidence of coercion and Notary negligence, resulting in civil, administrative and even criminal liability for the Notary.